2020
DOI: 10.1016/j.ijscr.2020.09.132
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis: Expect the unexpected

Abstract: Highlights Necrotizing Fasciitis is a rapidly progressive and potentially lethal soft tissue infection, aggressive surgical debridement supplemented with culture sensitive antibiotics is essential. Skin and soft tissue infections due to non-typhoidal salmonella present as subcutaneous abscesses in the vicinity of the G.I tract or as a wound infection post-surgery on a contaminated organ. Salmonella Newport has recently been implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Necrotizing fasciitis (NF) infections are rare and severe soft tissue infections characterized by rapid, progressive spreading among deep and superficial fascia and subcutaneous tissue, which can lead to shock and sepsis with multiorgan failure and a potentially fatal outcome [1]. Initial symptoms are tissue swelling, erythema, crepitations, fever, tenderness, odor, pain, bullous changes, and skin necrosis [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Necrotizing fasciitis (NF) infections are rare and severe soft tissue infections characterized by rapid, progressive spreading among deep and superficial fascia and subcutaneous tissue, which can lead to shock and sepsis with multiorgan failure and a potentially fatal outcome [1]. Initial symptoms are tissue swelling, erythema, crepitations, fever, tenderness, odor, pain, bullous changes, and skin necrosis [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…19 With regard to considering the optimal management, Khalid et al reported necrotizing soft tissue infections being associated with considerable morbidity and mortality, and delayed recognition and treatment can have severe implications. 20 As stated previously, Kihiczak et al have reported that prompt diagnosis and treatment are essential, with surgical debridement and antibiotic therapy are the primary treatment options. 7 Marszał and Bielecki stated early and radical surgical excision of all affected tissue is the treatment of choice.…”
Section: Discussionmentioning
confidence: 92%
“…Necrotizing fasciitis is a serious and potentially life-threatening soft tissue infection that should be promptly handled. A multidisciplinary team should be involved in managing this aggressive condition while continuously monitoring patient hemodynamics in a controlled setting [ 12 ]. NF is a surgical emergency requiring wide and extensive debridement and reconstructive surgery [ 13 ].…”
Section: Discussionmentioning
confidence: 99%